Effects of an autonomy support intervention on the involvement of higher education students (2021)
Intervention studies based on Self-Determination Theory (SDT) in educational contexts prove the importance of the teacher’s motivating interpersonal style, promoting positive results in students’ motivation. However, college practices and processes have new challenges. This study examines the repercussions of an intervention program with autonomy support on students’ involvement. The sample was randomly divided into two groups, an intervention group composed of 12 teachers, aged between 25 and 56 years (M = 35.38; SD = 7.71) and 113 students, aged between 18 and 28 years (M = 20.53; SD = 2.42); and a control group consisting of 12 teachers, aged between 25 and 44 years (M = 35.11; SD = 5.79), 107 students, aged between 18 and 39 years (M = 21; SD = 3.68). Quantitative and qualitative data were collected on the motivating interpersonal style, satisfaction of basic psychological needs, academic motivation and student involvement. The results demonstrate in general the effectiveness of the intervention on the perception of autonomy support to improve student involvement; this relationship is mediated by the improvement of psychological needs and academic motivation. The results are discussed around the recommendation of motivational strategies that the higher education teacher should implement to promote students’ involvement.